Richard Hingley. The Recovery of Roman Britain 1586-1906. A colony so fertile. Oxford, Oxford University Press, 2009, 390 pp. - Funari, Pedro Paulo A. (Revista Archai, 2011)
Richard Hingley. The Recovery of Roman Britain 1586-1906. A colony so fertile. Oxford, Oxford University Press, 2009, 390 pp.